Behavioral Contract Techniques in Reality Group Counseling as an Effort to Reduce Phubbing Behavior in High School Students - Pratiwi, Awalya Siska; Setiyowati, Arbin Janu (Journal of Education for Sustainability and Diversity, 2026)
This study aims to examine the effectiveness of the behavior contract technique in reality counseling as an effort to reduce phubbing behavior among high school students. Using a pretest-posttest quantitative research design on a control group, five students who were identified as having high phubbing behavior were selected as research subjects. The data collection instrument used was a validated phubbing behavior scale. The results showed a significant decrease in phubbing scores after the reality group counseling intervention was administered. Statistical analysis using the Wilcoxon Signed Ranks Test showed a Z value of -2.023 and a significance of 0.043 and indicated a significant effect of the intervention on reducing phubbing behavior. The findings of this study support the use of reality group counseling as an effective intervention strategy in schools to address phubbing behavior and improve students' psychosocial well-being.